Pengaruh Penerapan Model Pembelajaran Koopertif Tipe Think Pair Share (TPS) Terhadap Pemahaman Konsep Matematis Siswa Kelas X SMAN 1 Canduang Tahun Pelajaran 2012/2013 - Setiawan, Aris; Aima, Zulfitri; Pratiwi, Merina (STKIP PGRI Sumbar, 2013)
The research was motivated by student comprehension mathematical concept was low, and the smart students Â didnât want to share their knowledge with other students, so the Â result in learning mathematic class of students Â X SMAN 1 Canduang was low in academic year 2012/2013 . The purpose of this research to find out whether students comprehension mathematical concept by implementing cooperative learning model TPS was better thanÂ of used comprehension mathematical concept with conventional learning in class X SMAN 1 Canduang. The type of research was experimental research, the design of randomized trials on the subject . The population of this research was students of class X of SMAN 1 Canduang 2012/2013 academic year consisting of four classes. The ttechnique was random sampling , the sample was selected as the class, as a class experiment X3 and X2 as the control class . The instrument used in this study was written test essay form with reliability 0.72. The data of tests students in comprehension mathematical concepts was derived from the results of the final test comprehension mathematical concept. Based on the results of a quantitative analysis , the test of data to comprehension mathematical concepts , it is known that the two classes were normally distributed and the sample was not homogeneous on the real level Î± was 0.05 . Hypothesis was testing using the t test of the parties, obtained t was 5.354, so the research hypothesis was accepted . It can be concluded that the students comprehension of mathematical concepts by implementing cooperative learning model TPS was better Â than students to comprehension mathematical concepts with conventional teaching class X SMAN 1 Canduang.